Apollonius and the Golden Fleece:: A neo-mythological screen legacy - Winkler, Martin M. (Revista Archai, 2017)
A number of ancient poets and painters described or showed the Golden Fleece, one of the most intriguing supernatural objects in classical myth. But the poets were not as specific as their modern readers may wish. By contrast, cinema and television show the Fleece in all its specific aspects. Moving-image adaptations of classical myths always change their sources, a phenomenon usefully termed “neo-mythologism,” but they display the Fleece to good effect, if often in a variety of recreations. The seven European and American films examined here show us why the Fleece deserves the Homeric epithet thauma idesthai.